The epidemiology of electronic cigarette smoking among university students in the West Bank: Practice, motivation, and dependence of a new emerging hazard - Muhyee E. Jaber; Laith Nouri; Alaa Hamed; Noureldin Jarrar; Majdeddin MohammedAli; Motaz Saifi; Lubna Saudi; Basma Damiri (Population Medicine)
Introduction Tobacco smoking has reached an alarming rate among the young Palestinian population, specifically university students. Electronic cigarettes, or “e-cigarettes,” are an emerging hazard in the West Bank. However, the epidemiology of e-cigarette smoking among Palestinians is poorly described. Therefore, we aimed to determine the prevalence, pattern, motivation, dependence, and readiness to quit e-cigarette smoking among male university students.